Global sociology : - Schneider, Linda (McGraw-Hill Companies, 2010)
An effective supplement to any standard sociology text, this broad and comprehensive sociological description of five diverse contemporary societies with wide geographic distribution - Japan, Mexico, Egypt, Germany, and the Bushmen of Namibia - is organized around basic sociological topics: culture, social structure, group life, socialization, deviance, social institutions, social stratification, and social change. Fictional vignettes of individuals in each country help students experience first-person viewpoints on life in five very different societies. By comparing other societies with their own, students read about the range of social variation, learn what makes their own society distinctive, and gain a unique and fascinating vantage point on what sociology offers in a world of rapid social change. The fifth edition has been fully updated to reflect recent economic and political changes. New and updated data is included in each chapter. Current concerns such as crime, drug trafficking, ethnic diversity, gender, income inequality, political Islam and social change in traditional societies are addressed throughout the book.